Diseases of Banana, Abaca and Enset - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A valuable and comprehensive diagnostic tool describing many diseases, disorders and injuries, with 260 colour illustrations.Edited by D R Jones. CABI, 1999, 544 pp.ISBN 0 85199 355 9£85 Euro 160. See earlier CABI reference for address.Also...